2007
DOI: 10.1007/s00264-006-0304-7
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of transtrochanteric fractures of the femur with a minimally invasive technique using an extramedullary implant MINUS System

Abstract: We report here the results of a retrospective study on 120 patients treated for transtrochanteric fractures of the femur using a minimally invasive technique with an extramedullary sliding pin as implant -which we denoted the MINUS System. The evaluation was carried out in in the postoperative period, and the levels of haemoglobin (Hb) and haematocrit (Ht), surgical time, radiological screening time and pain levels were recorded. Prior to the operation, mean Hb and Ht were 11.69 g/dl and 35.72%, respectively; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The dynamic hip screw (DHS) with a four-hole side-plate and four bicortical screws is still considered to be a standard implant for pertrochanteric fractures (AO/ASIF 31A1+2) [3,7,8,10,[12][13][14][15]. The disadvantage of a four-hole sideplate as compared to a two-hole side-plate, as reported in the literature, is a longer incision, more invasive dissection of soft tissues associated with more intensive bleeding, longer surgical time and greater postoperative pain [1,4,6,9,16].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic hip screw (DHS) with a four-hole side-plate and four bicortical screws is still considered to be a standard implant for pertrochanteric fractures (AO/ASIF 31A1+2) [3,7,8,10,[12][13][14][15]. The disadvantage of a four-hole sideplate as compared to a two-hole side-plate, as reported in the literature, is a longer incision, more invasive dissection of soft tissues associated with more intensive bleeding, longer surgical time and greater postoperative pain [1,4,6,9,16].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment that is best for transtrochanteric fractures of the femur, taking into account unstable fractures in particular, is still a matter for debate in the literature. The choice between extra and intramedullary systems is based not only on the stability factor but also on the biological advantage 5 , 13 , 14 , 15 , 16 and the final cost of the procedure 16 , 17 , 18 . Several studies have compared the two systems and have not found significant differences in relation to length of the surgery, blood loss, consolidation and postoperative mortality 18 , 19 , 20 .…”
Section: Final Remarksmentioning
confidence: 99%
“…The choice between extra and intramedullary systems is based not only on the stability factor but also on the biological advantage (5,(13)(14)(15)(16) and the final cost of the procedure (16)(17)(18) . …”
Section: Final Remarksmentioning
confidence: 99%